Menciptakan Ruang Terbuka Hijau dengan Persepsi Keamanan sebagai Elemen Inklusif - Indah Rahmahdini; Aang Anggara; Suzana Margareth Aror (Program Studi Teknik Arsitektur, Fakultas Teknik, Universitas Sriwijaya, 2024)
Various solutions to urban problems caused by increased urbanization have been tried, including a sustainable development strategy. Point 11 of the Sustainable Development Goals calls for urban development to focus on creating inclusive, safe, resilient, and sustainable settings. Green open space is a vital urban environment for people's lives, and providing it does not mean sacrificing inclusive aims, such as the establishment of safe and sustainable spaces. The purpose of this study is to identify common ground on how to organize the provision of green open space in metropolitan areas in such a way that it is inclusive and boosts users' perceptions of safety. This study employed a comprehensive literature review approach. The collected literature is based on commonalities in study objectives, and the outcomes are compared to draw conclusions from this research. According to the results of the literature review, inclusive and safe public places are connected concepts. Designing security facilities in green open spaces can help to improve inclusion. Furthermore, the process of developing safe green open spaces indirectly improves the space's social performance, resulting in the creation of inclusive green spaces.